2020
DOI: 10.2967/jnumed.120.248278
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Monitoring of Immunotherapy and Targeted Therapy Using 18F-FET PET in Patients with Melanoma and Lung Cancer Brain Metastases: Initial Experiences

Abstract: Purpose: We investigated the value of O-(2-[ 18 F]fluoroethyl)-L-tyrosine ( 18 F-FET) PET for treatment monitoring of immune checkpoint inhibition (ICI) or targeted therapy (TT) alone or in combination with radiotherapy in patients with brain metastases (BM) since contrastenhanced MRI often remains inconclusive. Methods: We retrospectively identified 40 patients with 107 BM secondary to melanoma (n=29 with 75 BM) or non-small cell lung cancer (n=11 with 32 BM) treated with ICI or TT who had 18 F-FET PET (n=60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Perfusion MRI and MRI spectroscopy are increasingly used in this setting, but evidence for their ability to aid in differential diagnosis remains low [84] for correct differentiation are in the range of 80%-90% [87]. Furthermore, amino acid PET using FET is also of value for the diagnosis of treatment-related changes following immunotherapy, using immune checkpoint inhibitors or targeted therapy, with or without RT [EANO III, C; ESMO IV, C] [88].…”
Section: Monitoring and Follow-upmentioning
confidence: 99%
“…Perfusion MRI and MRI spectroscopy are increasingly used in this setting, but evidence for their ability to aid in differential diagnosis remains low [84] for correct differentiation are in the range of 80%-90% [87]. Furthermore, amino acid PET using FET is also of value for the diagnosis of treatment-related changes following immunotherapy, using immune checkpoint inhibitors or targeted therapy, with or without RT [EANO III, C; ESMO IV, C] [88].…”
Section: Monitoring and Follow-upmentioning
confidence: 99%
“…PET imaging is currently being evaluated to assess treatment responses and preliminary results, with amino acid PET to monitor immune checkpoint inhibition and targeted therapy appearing promising [ 97 ].…”
Section: Current Uses Of Pet Imaging In Brain Tumorsmentioning
confidence: 99%
“…A subsequent case report revealed a reduction in metabolic activity on AA-PET in a patient undergoing targeted therapy for non-small-cell lung cancer brain metastases indicating tumor response, while MR findings remained unchanged [ 52 ]. A recent study in a larger series of patients ( n = 40) with more than 100 brain metastases secondary to melanoma or non-small cell lung carcinoma treated with checkpoint inhibitors or targeted therapy combined with radiosurgery reported that 18 F-FET PET provides important diagnostic information in terms of response assessment [ 53 ]. Moreover, in that study, metabolic responders on 18 F-FET PET had a significantly longer progression-free survival in contrast to response determination based on contrast-enhanced MRI.…”
Section: Clinical Value Of Pet In Patients With Brain Metastasesmentioning
confidence: 99%